Growth stanzas in an Epinephelidae-Lutjanidae complex: considerations to length-weight relationships - Renán, Ximena (2015)
Growth stanzas or abrupt changes in growth rates are present throughout the life span of fish. Identifying growth stanzas will help to adequately described growth taking into account that fishes are indeterminate growers. In this study, we used length-weight (L-W) relationships to analyze the growth stanzas in the Grouper-Snapper complex of Southern Gulf of Mexico. For this, the type of sexuality, sex and different sexual maturity phase were considered in the analyses of three species of gonochoric Snappers (Lutjanidae) and six species of protogynous hermaphrodite Groupers (Epinephelidae). Welch ANOVA tests were carried out to determine the existence of differences in length and weight between juveniles and adults per sex. According to the observed differences, L-W relationship parameters (a and b), standard error (SE b) and coefficients of determination (R2) were calculated for all species separately by sex and sexual maturity phase. Snappers’ juvenile-females b-value ranged for 2.44-2.77, juvenile-males from 2.16-2.94, adult-females from 2.63-2.80 and adult-males form 2.63-2.98. Groupers’ b-value ranged for juvenile-females 2.66-3.20, adult-females from 2.73-3.31 and for adult-males 2.93-3.29. For each relationship b-value was t-tested (t-Student) to explore differences from the allometric coefficient (b=3), which indicated changes in body form. Hypothesis test, for regression slopes (b) between Snappers’ juvenile-females vs. adult-females and juvenile-males vs. adult-males and Groupers’ juvenile-females vs. adult-females and adult-females vs. adult-males, indicated different growth stanzas related to gonadal development for Snappers, and to gonadal development and sex change in Groupers. The identification of growth stanzas is crucial to avoid an overestimation or misleading growth rate which is used in fisheries management to establish some target reference points, such as maximum sustainable yield or yield-per-recruit.